LITERASI MEDIA DAN PENTINGNYA PARENTING DALAM PENGGUNAAN GAWAI DARING PADA WARGA DURI KEPA JAKARTA BARAT - Vardiansyah, Dani (Jurnal Pengabdian Masyarakat AbdiMas, 2018)
AbstractAgainst the background of the widespread use of online media devices that have penetrated all levels of society, it is felt necessary to foster a proper understanding of gadgetdigital usage in order to avoid negative aspects of media content through literacy so parents take an active role in parenting monitoring the use of children's devices. This activity was a Community Service activity conducted by a lecturer with a number of 2015 Faculty of Communication Faculty Students, Esa Unggul University, Jakarta. The activity took place in RT 013 / RW 007 & RT 003 / RW 07, Duri Kepa Village, Kebon Jeruk District, West Jakarta. Literacy is done with focus group methods in several groups with an edutainment atmosphere. From the results of the activities obtained conclusions: 1) Many things from the use of devices by children that are not known and often overlooked by parents so that, with this activity, citizens understand the adverse effects of the use of devices and educate them on the importance of parenting the use of children's devices, 2) Parents are able to guide children in choosing and sorting out positive media content and fostering ethical behavior in the use of gadgets and legal consequences for violators. Keywords : media literacy, gadgets, media content violence AbstrakDilatarbelakangimaraknya penggunaan gawai (gadget) media daring (online)yang telah merambah ke seluruh lapisan masyarakat, dirasa perlu menumbuhkan pemahaman tepat terkait penggunaan gadgetdigitalguna menghindari aspek negatif muatan isi media melalui literasi agar orangtua mengambil peran aktif dalam parenting pengawasan penggunaan gawaianak. Kegiatan ini merupakan aktivitasPengabdian Kepada Masyarakat yang dilakukan Dosen bersamabeberapa Mahasiswa Fakultas Ilmu Komunikasi Angkatan Tahun 2015, Universitas Esa Unggul Jakarta.Aktivitas berlangsung di lingkungan RT 013/RW 007 & RT 003/RW 07, Kelurahan Duri Kepa, Kecamatan Kebon Jeruk, Jakarta Barat.Literasidilakukan dengan metode focus groupdalam beberapa kelompokdengan suasana edutainment. Dari hasil kegiatan diperoleh simpulan: 1) Banyak hal dari penggunaan gawai oleh anak yang belum diketahui dan sering diabaikan orangtuasehingga, dengan kegiatan ini,warga memahami dampakburuk penggunaan gawaiserta mengedukasimereka akan pentingnya parentingpenggunaan gawai anak,2)Orangtua mampu membimbinganak dalammemilih dan memilah muatan positif media serta menumbuhkanperilaku beretika dalam penggunaan gadget berikut konsekwensi hukum atas pelanggarnya. Kata kunci: literasi media, gadget, kekerasan isi media